The Emergence of Somatic Psychology and Bodymind Therapy - Barratt, B. author. aut Link
VIII, 234 p.
Keywords: Somatic psychology and bodymind therapy (the simultaneous study of the mind and body) are challenging contemporary understandings of the psyche, of what it means to be human and how to heal human suffering.